Pengaruh Etika Bisnis, Corporate Social Responsibility (Csr), Terhadap Kinerja Keuangan Pada Perusahaan Industri Barang Konsumsi Yang Terdaftar Di Bei Tahun 2019 - 2023 - Hafni, Naina Yulia; Purba, Rahima Br (Jurnal Mirai Management, 2025)
This study was conducted to analyze the influence of Business Ethics, Corporate Social Responsibility (CSR) on Financial Performance. The location of this study is a Consumer Goods Manufacturing Company listed on the Indonesia Stock Exchange. This type of research is Associative research with a quantitative approach. Until this study, there were 27 companies with a time period of 5 years, namely 2019 to 2023, resulting in 135 financial reports. The method used is panel data regression analysis with the help of IBM SPSS Statistics 23 software. The results of this study indicate that partially Business Ethics has no effect on Return On Asset, Corporate Social Responsibility partially has a positive effect on Return On Asset. While simultaneously all variables of Business Ethics and Corporate Social Responsibility, simultaneously affect Return On Asset. The contribution of the influence of the variables is 7.6%. Kata kunci : Return On Asset, Etika Bisnis, Corporate Social Responbility